Miradas sobre el reencuentro: dos contextos de devolución de las fotografías Yaganes tomadas por Martin Gusinde (1918-1923) - Ramírez, Daniella (Revista Mundaú, 2018)
This article analyzes two experiences of returning photographs to the yagans - indigenous hare of southern Patagonia - taken by Martin Gusinde, anthropologist and Austrian priest, to their context of origin. The first return, made from his trips to the extreme Chilean and Argentinean between 1918 and 1923; The second, held between 2012 and 2014 as part of the joint work of the Martín Gusinde Anthropological Museum with the yagán indigenous community (Puerto Williams, Chile). In this circuit, photography is a visual medium that depends on the place of enunciation to be reactualized and resignified. The "reencounter" presupposes a reading in front of the circulation circuits of the archive, the ethnographic text and the museum, thus confirming that there are transits of sense of the image, from which tensions arise on the imaginary Fuegian, as well as stories And family and regional memories.